Best m-term approximation of the classes B ^r_∞, θ of functions of many variables by polynomials in the haar system - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain the exact-order estimate for the best m-term approximation of the classes B ^r_∞, θ of periodic functions of many variables by polynomials with respect to the Haar system in the metric of the space L_q,1 < q < ∞.